Manipulating the flow over a circular cylinder with control rods. - Cicolin, Murilo Marangon (2021)
The flow past a circular cylinder with control rods at moderate values of Reynolds number is experimentally investigated in this work. The flow topology depends on many parameters, such as Reynolds number (Re), the ratio between the diameter of the cylinders (d/D), number and position of the rods. Preliminary experiments on the sensitivity of fluid forces have shown that the rods position is the most relevant among all the parameters tested. The hydrodynamic forces suffer the greatest variation when the rod is placed close to the shear layers or the cylinders surface. Detailed investigation of the wake with one-rod using fixed values of Re = 20, 000, and d/D = 0.1 has shown that the wake developed three distinct states, depending on the rods angular position . State I is characterised by two distinct vortex streets, downstream of the cylinder and rod, respectively. State II is characterised by a strong jet between the cylinder and the rod and a late separation due to Coanda effect. And in State III the rod acts in the recirculation region, with a relatively lower influence in the flow compared to the other states. In addition, a bi-stable case was observed between the states II and III, with no clear switching frequency between the states and very sensitive to the rods position. Adding a second and symmetrical rod to the system turns the mean flow symmetric for States I and III, whereas State II shows an asymmetric mean wake due to a bi-stable behaviour induced by the imbalance of the jets in the near wake. A transitional case was observed between State I and II, with a type of separation not observed for one-rod cases, which showed a reduction of 90% in the fluctuating lift force.The position of the separation point varied significantly for States I and II compared to that of a bare cylinder. It prompted a significant impact on the hydrodynamic forces acting on the cylinder. The greatest reductions of the mean drag force were observed for State II cases with two-rod: 20% for the combined system and 30% for the main cylinder, both with respect to the bare cylinder case.